2012
DOI: 10.1002/job.1771
|View full text |Cite
|
Sign up to set email alerts
|

How do transformational leaders foster positive employee outcomes? A self‐determination‐based analysis of employees' needs as mediating links

Abstract: Summary Although followers' needs are a central aspect of transformational leadership theory, little is known about their role as mediating mechanisms for this leadership style. The present research thus seeks to integrate and extend theorizing on transformational leadership and self‐determination. In particular, we propose that the satisfaction of followers' basic needs (autonomy, competence, and relatedness) mediates the relationship between transformational leadership and employee outcomes (job satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
175
1
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(198 citation statements)
references
References 70 publications
12
175
1
10
Order By: Relevance
“…Consistent with this position, Van der Heijden and Bakker (2011) found that transformational leadership had a positive impact on work-related flow. Transformational leaders also facilitate the basic needs satisfaction of their followers by providing them with feedback, tasks that match their abilities, and job control, thereby playing to their needs for competence and autonomy (Hetland et al 2015;Kovjanic et al 2012). The need for relatedness is satisfied by giving personal attention and social support (Breevaart et al 2014a;Deci and Vansteenkiste 2004;Kovjanic et al 2012).…”
Section: Organizational Contextmentioning
confidence: 99%
“…Consistent with this position, Van der Heijden and Bakker (2011) found that transformational leadership had a positive impact on work-related flow. Transformational leaders also facilitate the basic needs satisfaction of their followers by providing them with feedback, tasks that match their abilities, and job control, thereby playing to their needs for competence and autonomy (Hetland et al 2015;Kovjanic et al 2012). The need for relatedness is satisfied by giving personal attention and social support (Breevaart et al 2014a;Deci and Vansteenkiste 2004;Kovjanic et al 2012).…”
Section: Organizational Contextmentioning
confidence: 99%
“…Much research has contributed useful insights to the former, the impact of transformational leadership on employee creativity by demonstrating the mediating influences of intrinsic motivation (Shin & Zhou, 2003), confidence in creative performance (Gong et al, 2009), needs satisfaction (Kovjanic, Schuh, Jonas, Quaquebeke, & Dick, 2012), and work engagement (Aryee, Walumbwa, Zhou, & Hartnell, 2012). However, less is known about the latter, how transformational leadership may have an impact on employee creativity via its influence on employee's social environment such as group climate.…”
Section: Introductionmentioning
confidence: 99%
“…При этом у нас нет оснований полностью отрицать результаты предшествующих ис-следований, которые показали значимость как индивидуальных характеристик субъ-екта восприятия (высокий уровень добро-желательности), так и перцепционных фак-торов (позитивное эмоциональное воспри-ятие руководителя) [ElKordy, 2013;Schyns, Sanders, 2007;Kovjanic et al, 2012;UhlBien et al, 2014;Stelmokienė, En driu laitienė, 2015]. Подчиненные считают, что работают под руководством трансформа-ционного лидера, в условиях эмоциональ-но позитивной атмосферы, которую созда-ет их начальник и которая позволяет сгла-живать стрессы и конфликты в жестко конкурентной среде, предъявляющей вы-сокие требования к эффективности труда работников.…”
Section: результаты исследованияunclassified